ANALISIS PENGARUH INFLASI, BI RATE, NILAI TUKAR KURS, INDEKS HANG SENG DAN INDEKS DOW JONES TERHADAP RETURN SAHAM (STUDI EMPIRIS PT. SEMEN INDONESIA PERIODE 2009-2016) - Erga Armela Febrianti; Abd. Rohman Taufiq (Universitas PGRI Madiun, 2018)
This study aims to provide empirical evidence of partial or simultaneous influence between Inflation, BI Rate, Exchange Rate, Hang Seng Index and Dow Jones Index on Stock Return (Empirical Study of PT. Semen Indonesia Period 2009-2016). The type of research used in this study is quantitative research. Population in this research is PT. Semen Indonesia The Period 2009-2016). The number of samples is 32. Data analysis used is descriptive statistics, classical assumption test, multiple linear regression, and hypothesis test using SPSS version 16.0. The simultaneous test results (F test) of allvariables Inflation, BI Rate, Exchange Rate, Hang Seng Index and Dow Jones Index simultaneously affect the Stock Return of Share of 4.781.Keywords: Inflation, BI Rate, Exchange Rate, Hang Seng Index, Dow Jones Index,Stock Return.